PENGARUH KUALITAS AUDIT TERHADAP PENGUNGKAPAN KECURANGAN LAPORAN KEUANGAN PERUSAHAAN - Naili Saadah (Fakultas Ekonomi Universitas Pekalongan, 2018)
This study aims to examine the empirical facts of the two theories that are used side by side, namely agency theory and positive accounting theory within the scope of the problem that is based on the influence of audit quality on disclosure of fraudulent investor financial and perspective reports. This study uses secondary data sources originating from IDX and literature. The analysis tool used to test the relationship between variables is multiple regression where the results of this study show two proofs that audit quality has a positive effect on the level of investor perceptions as measured by the cost of equity capital but conversely audit quality does not significantly influence earnings management. this can be interpreted that high audit quality can increase investor confidence so that it has an impact on the high cost of equity capital but high audit quality does not have a significant impact on earnings management practices.Keywords: AuditQuality, audit tenure, the cost of equity capital and earnings management